2022
DOI: 10.21037/tcr-21-2021
|View full text |Cite
|
Sign up to set email alerts
|

GABRP is a potential prognostic biomarker and correlated with immune infiltration and tumor microenvironment in pancreatic cancer

Abstract: Background: Pancreatic cancer is one of the most commonly diagnosed and lethal malignancies worldwide and has few good biomarkers and therapeutic targets. GABRP is the π subunit of the gamma-aminobutyric acid (GABA) A receptor, which is expressed in a number of non-neuronal tissues. GABRP is significantly upregulated in pancreatic cancer, but its biological and immunological role as well as its clinical diagnostic and prognostic value in pancreatic cancer is still incompletely known.Methods: In this study, pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…GABRP was up-regulated in pancreatic cancer, and it was an independent prognostic biomarker for pancreatic cancer patients, this result was consistent with our study. 11 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GABRP was up-regulated in pancreatic cancer, and it was an independent prognostic biomarker for pancreatic cancer patients, this result was consistent with our study. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 7 GABRP was associated with tumor microenvironment and immune cell infiltration in pancreatic cancer. 11 In addition, the survival advantage of lung cancer patients may be associated with the anti-cancer effect of CD8+/IL-10+ cell phenotype. 20 Previous studies have demonstrated that NK cells could infiltrate lung tumor, implying that the infiltrations of NK cells into cancer cells may benefit the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AURKA mutation had no effect on overall survival time, but impacted the progression free survival time (p = 0.0269). A number of cancer treatments have shown great clinical bene ts from immune checkpoint therapy (ICT) over the past few years [24], solid tumors with macrophage in ltration had poor survival outcomes while those with CD8 + T cells were more likely to survivet [25; 26]. Consequently, we compared immune in ltration landscapes in colorectal cancer and normal populations.…”
Section: Discussionmentioning
confidence: 99%